Comparison of two compounding techniques for carbon nanotubes filled natural rubbers through microscopic and dynamic mechanical characterizations - Ali Esmaeili (Materials Letters, 2023)
Natural rubber used in wave energy converters requires higher fatigue life and better energy harvesting efficiency to make it inexpensive compared to other renewable energy resources. Carbon nanotubes (CNTs) were extensively used to enhance the mechanical properties of natural rubber, however, its performance in a double-bonded shear condition was rarely investigated. In addition, the state of CNT dispersion was a critical factor for better energy harvesting efficiency and fatigue life. Therefore, this study was aimed to compare two different dispersion approaches in CNT synthesis so that better dynamic mechanical properties and lower hysteresis loss were achieved. One approach was done in the liquid state whereas the other one was carried out in dry condition. Although the former manifested a better CNT dispersion, no significant differences in terms of dynamic mechanical properties and dissipation losses compared to the latter compounding were obtained.